PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA EDUKATIF DALAM MENGENALKAN SIKAP PATUH ATURAN PADA MATERI “AKU PATUH ATURAN DI RUMAHKU” PENDIDIKAN PANCASILA UNTUK KELAS 1 SD - Sekar Dhiani, Nayya Kinara; Marini, Arita; Hadi, Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to develop an educational Snakes and Ladders game-based learning media for the Pancasila Education subject, specifically on the topic “I Obey the Rules in My Home”, for first-grade elementary school students. The background of this research was based on the condition that Pancasila Education learning is still predominantly conducted through lecture-based methods, causing normative and abstract materials to be less contextually understood by students. The method used in this research was Research and Development (R&D) employing the ADDIE development model, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. The research subjects were 14 first-grade students of MIN 12 East Jakarta. The research instruments included material and media expert validation questionnaires using a Likert scale, as well as student response questionnaires using a Guttman scale. The results of the material expert validation obtained a percentage of 100%, while the media expert validation obtained a percentage of 95.8%, both categorized as “very good.” The results of the student response questionnaire showed a percentage of 96.4%, which was also categorized as “very good.” Based on these findings, the educational Snakes and Ladders learning media was declared valid, feasible, and effective for use in Pancasila Education learning for first-grade elementary school students to foster understanding and habituation of rule-based values among students.